Ultrastable Perovskites: Strain‐Mediated Phase Stabilization: A New Strategy for Ultrastable α‐CsPbI3 Perovskite by Nanoconfined Growth (Small 21/2019). Issue 21 (24th May 2019) - Ma, Sunihl; Kim, Seong Hun; Jeong, Beomjin; Kwon, Hyeok‐Chan; Yun, Seong‐Cheol; Jang, Gyumin; Yang, Hyunha; Park, Cheolmin; Lee, Donghwa; Moon, Jooho
Abstract : In article number1900219, Donghwa Lee, Jooho Moon, and co‐workers develop an approach to stabilize α ‐CsPbI3 perovskite through strain engineering, whereby CsPbI3 perovskite is confined by a vertically aligned nanoporous template. By imposing a strain on the perovskite lattice, the ultra‐stable black α ‐CsPbI3 with its desirable optoelectrical properties is obtained. This universally applicable template‐based stabilization strategy provides in‐depth insights on the strain‐mediated phase transition mechanism in all‐inorganic perovskite.